Right ventricular structure and function in senior and academy elite footballers. (2nd September 2018) - Popple, Emily; George, Keith; Somauroo, John; Sharma, Sanjay; Utomi, Victor; Lord, Rachel; Cooper, Robert; Malhotra, Aneil; Forster, Jan; Oxborough, David
Abstract: Aims: Right ventricular (RV) adaptation is a common finding in the athlete's heart. The aim of this study was to establish the extent of RV structural and functional adaptation in elite and academy professional footballers compared to age‐matched controls. Methods and Results: A total of 100 senior and 100 academy elite footballers and 20 senior and 19 academy age‐matched controls were recruited. All participants underwent 2D, Doppler, tissue Doppler, and strain (ε) echocardiography of the right heart. Structural indices were derived and indexed allometrically for individual differences in body surface area. Standard RV function was assessed alongside peak RV ε and strain rate (SR). Senior football players had larger scaled RV structural parameters than academy players for the RV outflow (RVOTplax ) (32.7 ± 4.2 and 29.5 ± 4.0 mm(m 2 ) 0.326, P  <   0.001), the proximal RV outflow (RVOT1 ) (26.6 ± 3.5 and 24.7 ± 3.9 mm(m 2 ) 0.335, P  <   0.001), the basal RV inflow (RVD1 ) (33.1 ± 4.1 and 30.7 ± 3.2 mm(m 2 ) 0.404, P  =   0.020), RV length (RVD3 ) (66.5 ± 6.1 and 62.9 ± 5.1 mm(m 2 ) 0.431, P  <   0.001), and RV diastolic area (RVDarea ) (16.9 ± 2.6 and 15.7 ± 2.6 mm(m 2 ) 0.735, P  <   0.001). Both academy and senior football players demonstrated larger scaled structural RV parameters in comparison with age‐matched controls. Systolic SR (SRS) was lower in the senior players compared to academy players in the mid (−1.52 ± 0.49 and −1.41 ± 0.34 L/s, P  =   0.019) and apical (−1.97 ± 0.74 and −1.72 ± 0.42 L/s, P  =   0.025) wall regions, respectively. Conclusion: Right ventricular structural adaptation occurs in both senior and academy football players with senior players having larger RV dimensions. Although senior players have slightly lower peak SRS than academy players, all global ε and SR are within normal ranges.